Characterization of a nifH-Harboring Bacterial Community in the Soil-Limited Gotjawal Forest - Lee, Tae Kwon; Han, Il; Kim, Min Sung; Seong, Hoon Je; Kim, Jong-Shik; Sul, Woo Jun (Frontiers in Microbiology, 2019)
Using a high-throughput metagenomic approach, we evaluated nifH-harboring bacterial communities and their assembly in the Gotjawal forest, which was naturally formed on basalt rocks with thin layer of soil. Significant differences in soil properties and community structure were observed in comparison with similar communities in various habitats, including other lava-formed forests (on Jeju Island and in Hawaii) and in regions with high humidity (Florida) or low temperatures (Alaska). nifH-harboring bacterial communities were found to assemble along gradients of environmental factors, particularly cation-exchange capacity. Unlike in other regions, in the Gotjawal forest, Paenibacillus and Clostridium, which belong to the phylum Firmicutes, were present in significantly higher proportion than in other regions. Network analysis suggested that much fewer co-occurrence relationships occurred in the Gotjawal forest than in other lava-formed forests. Our results indicate that the unique nifH-harboring bacterial community and its assembly in the Gotjawal forest are due to its distinctive soil properties, which has implications for microbial interactions and functional potentials.